(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study looked at the impact of learning management systems towards a guide. As in our current pandemic situation, face-to-face classes are still not permitted, which is why technology and LMS are very useful for students and instructors, as they can meet via platforms like Zoom, Google Meet, or any meeting application required by the school. A learning management system is software used to administer, record, monitor, report on, automate, and deliver educational programs for learning and development. The learning management system concept emerged directly from e-learning. This study utilized the descriptive method design to investigate and collect information about the impact of the learning management system as perceived by the BSHM students. To collect data, the researchers used survey questions distributed via Google Forms to 100 respondents at Bestlink College of the Philippines. The results of the survey revealed that the majority of the respondents are in the age group of 22-24. Female is 55%, male is 44%, and 1% prefer not to say. Among the 100 respondents, 80% are 4th year, 19% are 3rd year, and 1% remaining are 2nd year, and all of the respondents are single. As in our current pandemic, the learning management system has a positive effect on the students because they can easily access it anywhere, they do not need to go to school to get the materials personally, and it manages time efficiently. The impacts of the learning management system on the BSHM students as to distribution, resources, schedule, assessment, communication, and feedback, with a weighted mean of 3.89. Challenges and effects of learning management system in terms of accessibility and level of usefulness with a weighted mean of 3.96 followed by utilized crafting guidelines of learning management system with a weighted mean of 3.96. It indicates that the participation and collaboration of the institution, the teacher, and the parents will help the students cope with the new way of learning in today’s situation brought about by the pandemic. Students will benefit from using resources such as learning management systems and various social media platforms for distance learning, as well as the continual support and guidance of the people mentioned, especially when they are still determining the relevance of such resources to their studies. A learning management system’s impact on a guide can be identified and resolved using various methods and approaches.